2007
DOI: 10.2172/917412
|View full text |Cite
|
Sign up to set email alerts
|

Demand Controlled Filtration in an Industrial Cleanroom

Abstract: In an industrial cleanroom, significant energy savings were realized by implementing two types of demand controlled filtration (DCF) strategies, one based on particle counts and one on occupancy. With each strategy the speed of the recirculation fan filter units was reduced to save energy. When the control was based on particle counts, the energy use was 60% of the baseline configuration of continuous fan operation. With simple occupancy sensors, the energy usage was 63% of the baseline configuration. During t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The calculated DCF energy savings for Case study H ( Table 3 ) were higher than in other studies [13,[16][17][18] . The main reason for this was that the two rooms of Case study H showed a very low use time.…”
Section: Acr Optimizationmentioning
confidence: 59%
See 2 more Smart Citations
“…The calculated DCF energy savings for Case study H ( Table 3 ) were higher than in other studies [13,[16][17][18] . The main reason for this was that the two rooms of Case study H showed a very low use time.…”
Section: Acr Optimizationmentioning
confidence: 59%
“…No sources need be assumed when the cleanroom is unoccupied. The control then simplifies considerably (occupied/unoccupied: ON/OFF), as do the investment costs [16] . If a production process has activities which are not directly coupled to persons present in the cleanroom, control on particle concentration may still present a feasible alternative.…”
Section: Acr Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In our building, there are 25 RAHU units, each consuming 2-3 kW, with a total aggregate airflow of around 215000 cfm; this dwarfs the airflow in our 10 conference and class rooms, which is a total of about 5000 cfm. The potential to curtail RAHU operation when the cleanrooms are not in use could save large amounts of power; this is called demand-controlled filtration (DCF) [72].…”
Section: B Demand-controlled Filtrationmentioning
confidence: 99%
“…That of the facilities benchmarked, half were operating below the lower range of typical practice (250 ACH) shows that great progress can be made by attending to a few especially energyintensive facilities (13). Real-time particle counting can be used to modulate ventilation speeds, thereby better managing energy demand (38). Expanded-area filtering can save energy by reducing pressure-drop and trim waste and maintenance costs thanks to less frequent replacement needs.…”
Section: Clean Environmentsmentioning
confidence: 99%